(untitled) (Current Problems in Rail Vehicles, 2021)
The noise parameters of railway vehicles clearly contribute to their quality and are specifically monitored in accordance with the ever-tightening limits of TSIs or environmental regulation in general. The basis for the possibilities of reducing vehicle noise is a detailed analysis of noise sources and paths. The paper presents valuable results and new findings from acoustic experiments from the operation of trains at ŽSR using an acoustic camera.